THE FACTOR STRUCTURE OF THE AXIOPSYCHOLOGICAL DESIGN OF THE LIFE ACHIEVEMENTS AT LATE ADULTHOOD - Hulias, Inesa (PSYCHOLOGICAL JOURNAL, 2019)
The article studies the specifics of axiopsychological design of a person’s life achievements at his/her late adulthood. The basic psychological features of this age representatives are outlined. It is also essential, as the article emphases, that the structure of a person’s psychological time is changed considerably at late adulthood. The part of the future, which expanded a person’s life space, decreases sharply in the person’s chronotope. In addition, forced reduction of external activities, allows a person to expand and deepen the sphere of internal activities. Attention is focused on the fact that the main concern of a person in this life period should be the development of his/her spiritual sphere, his/her life in the space of the deep existential senses of an individual and humankind to understand the uniqueness of each individual, his/her irreplaceability, which softens the situation of uncertainty, gives the future some meaning. The article states that a person’s ability to design helps him/her to predict, on the probable basis, the results of both his/her own activity and that of other people and events. Predicting the possible degree of any goal achievement, under the conditions of a certain course of actions, is the content of the design process as a determinant of an individual’s life achievements. Within the context of the research methodology, the starting point is the concept on a personality as an integral agent of possible spiritual, moral and other deep transformations and object embodiments of a person; and the principles of subjectivity, value orientations, and teleological principles are the basis for the empirical study of the phenomenon. A particular attention is paid to the empirical research, the results of which are generalized and interpreted in the factor structure of an axiopsychological design of the respondents’ life achievements, represented by twelve components: successful implementation, result orientation, a regulatory resource, futile efforts, dispossession of self-efficiency, comfortable life, inverse femininity, promotion of activities, an external factor, curtailment of social roles, dissatisfaction with self-realization, desire for success. It has been found that the factor structure of the respondents’ value design is dominated by the first two, which can be considered to be the leading ones.